2020
DOI: 10.1088/2053-1591/ab6ace
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolic nitrogen-doped multiwall carbon nanotubes using ball-milled slag-SiC mixtures as a catalyst by aerosol assisted chemical vapor deposition

Abstract: We demonstrated that the ball-milled slag-SiC mixture is an effective catalyst to grow pyrrolic nitrogen-doped multiwall carbon nanotubes (N-MWCNTs) by aerosol assisted chemical vapor deposition (AACVD) method. N-MWCNTs synthesized at 800°C, 850°C and 900°C were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, x-ray powder diffraction (XRD), and x-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). TEM characterizations reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 104 publications
(129 reference statements)
3
0
0
Order By: Relevance
“…The increasing CVD temperature caused the CNFs to grow with wider diameter ranges, which is consistent with previous works. The higher CVD temperature causes catalyst particles to agglomerate, resulting in bigger catalyst particles generating CNFs with larger diameters . The higher temperature also causes catalyst droplets to become flat; thus, the precipitation area of carbon to deposit on the catalyst is enlarged, consequently growing bigger CNFs.…”
Section: Resultssupporting
confidence: 88%
“…The increasing CVD temperature caused the CNFs to grow with wider diameter ranges, which is consistent with previous works. The higher CVD temperature causes catalyst particles to agglomerate, resulting in bigger catalyst particles generating CNFs with larger diameters . The higher temperature also causes catalyst droplets to become flat; thus, the precipitation area of carbon to deposit on the catalyst is enlarged, consequently growing bigger CNFs.…”
Section: Resultssupporting
confidence: 88%
“…This implied that the electrocatalytic activity was influenced more by the presence of pyrrolic nitrogen than by the total nitrogen content. These results are in line with those obtained by other studies, which have shown that nitrogen species and not just the nitrogen content in graphene-based materials play a significant role in influencing the electrocatalytic properties [32,33].…”
Section: Bioelectrocatalytic Properties Of Rgo and Rgo/organic-dye-co...supporting
confidence: 92%
“…In the composite rGO_NR, the N5 amount was 35.73%, and no amount was found in the composite rGO_CR (Figure 6). These findings confirm those of earlier studies, which have demonstrated that carbon-based materials with a relatively high content of pyrrolic nitrogen at the edges of graphene layers will show better charge mobility and donor-acceptor properties compared to pyridinic and graphitic nitrogen [31,32]. This implied that the electrocatalytic activity was influenced more by the presence of pyrrolic nitrogen than by the total nitrogen content.…”
Section: Bioelectrocatalytic Properties Of Rgo and Rgo/organic-dye-co...supporting
confidence: 91%